(untitled) - Tepper, Sheri S. (New York, 1987)
On the planet Jubal, human colonization has been restricted by massive crystalline "presences" which may or may not be sentient, but in order to protect them from destruction, they must be convinced to break their long silence.
Keywords: Science fiction, American,Tiểu thuyết khoa học, Hoa Kỳ,American fiction,Tiểu thuyết Mỹ